Force plate-derived isometric midthigh pull data in girls youth and adult soccer players: a comparison between age groups - Fahey, J. T.; Comfort, P.; Ripley, N. J. (The Journal of Strength and Conditioning Research, 2026)
Expression of maximal and rapid force (i.e., force at 250 ms) is important for sporting success. Despite growing participation rates, injury risk in women soccer remains high. Furthermore, relative strength does not seem to change across age groups with no current data on rapid force production. This study was designed to report net and relative net isometric midthigh pull (IMTP) peak and rapid force for girls youth soccer players. Ninety-four youth soccer players, categorized into Foundation Development Phase (FDP; U11-U12, n = 21, 10.9 ± 0.6 years, 42.8 ± 7.6 kg, 1.49 ± 0.08 m), Youth Development Phase (YDP; U13-U15, n = 35, 13.6 ± 1.0 years, 54.8 ± 7.9 kg, 1.60 ± 0.06 m), and Professional Development Phase (PDP; n = 38, U16-U21, 16.2 ± 1.1 years, 63.4 ± 6.8 kg, 1.67 ± 0.06 m) performed the IMTP. Moderate-to-large differences were observed between FDP vs. YDP and PDP for net peak force, relative net peak force, and relative net force at 250 ms, with no differences between YDP and PDP players, respectively. Small-to-moderate increases in relative net peak force were observed between FDP vs. YDP and PDP. The results of this study highlight that maximal and rapid relative strength plateaus with increasing age. This could be problematic for players aiming to transition to senior and international standards of women's football and warrants further investigation. Practitioners should design strength and conditioning programs to enhance maximal and rapid relative strength to physically prepare youth players for the increased match-demands associated with increasing age and competition.